Mesoporous Co@MCM-41 catalyst for stable ethane dehydrogenation - Xiufang Wang; Yufeng Li; Wenda Yu; Yuebing Xu; Bing Liu; Xiaohao Liu (Carbon Resources Conversion, 2025)
Catalytic dehydrogenation of low-cost C2-C4 alkanes can be an alternative route to produce value-added olefins. To overcome the drawback of a microporous Co-based Co@MFI zeolite catalyst that is sensitive to coke deposition for its deactivation, herein, a mesoporous Co-incorporated MCM-41 catalyst was synthesized by hydrothermal synthesis successfully and tested for ethane dehydrogenation. Various characterizations suggested that Co species were also dispersed in an atomical level in the MCM-41 zeolite with a reduction-resistant –Coδ+–Oδ-– structure, which, therefore, ensures its high selectivity to ethylene (∼100 %). Thanks to the mesoporous characteristic of the MCM-41, the as-synthesized Co@MCM-41 catalyst showed excellent stability than the widely reported microporous Co@MFI catalysts, which can be attributed to the reason that the mesoporous channels are not sensitive to coke deposition and still allow reactant and products to diffuse in and out easily, This work demonstrates the importance of the diffusion of a zeolite-based catalyst and promotes the application of Co-based catalyst for alkane dehydrogenation.